The California Tree Mortality Data Collection Network — Enhanced communication and collaboration among scientists and stakeholders - J Axelson; J Battles; B Bulaon; D Cluck; S Cousins; L Cox; B Estes; C Fettig; A Hefty; S Hishinuma; S Hood; S Kocher; et al. (California Agriculture)
Critical research and dialogue are underway to understand the consequences of the massive wave of tree mortality in the Sierra Nevada.